DNA Aptamer Based Nanodrugs: Molecular Engineering for Efficiency. Issue 10 (4th September 2015) - Cansiz, Sena; Zhang, Liqin; Wu, Cuichen; Wu, Yuan; Teng, I‐Ting; Hou, Weijia; Wang, Yanyue; Wan, Shuo; Cai, Ren; Jin, Chen; Liu, Qiaoling; Tan, Weihong
Abstract In the past two decades, the study of cancer therapy has gradually advanced to the "nano" era. Numerous novel nanomaterials armed with unique physical properties have been introduced into biomedical research. At the same time, functional nucleic acid molecules, especially aptamers, have aroused broad attention from the biomedical community. Benefiting from the advancement of molecular engineering strategies, it is now feasible to combine the cancer‐specific recognition capability of aptamers with various other special functions of nanomaterials to develop cancer‐specific drugs at the nanoscale. Nanodrugs are now offering an unprecedented opportunity to achieve the goal of efficient targeted delivery as well as controlled release. This review highlights some achievements made in multiple aptamer‐based nanodrug systems that have emerged in recent years, including studies in the infant stage of "proof‐of‐concept".